Integrative-Intersubjective Type of Islamic Law Studies: The Shifting of Paradigms in Epistemology of Islamic Law at the Faculty of Sharī’a and Law, Sunan Kalijaga State Islamic University, Indonesia - Riyanto, Waryani Fajar (UIN Sunan Kalijaga, 2024)
The epistemology of Islamic law studies has shifted from an atomization model towards an integration one. The integration of Islamic law epistemology includes the subjective, objective, and intersubjective types. The epistemological integration model in this field has become a crucial discourse at the State Islamic University (Universitas Islam Negeri – UIN) of Sunan Kalijaga, Yogyakarta, Indonesia. Accordingly, the current article discusses the shifting of paradigms in epistemology of Islamic law studies at the Faculty of Sharī’a and Law (Fakultas Sharī’ah dan Hukum - FSH) UIN Sunan Kalijaga of Yogyakarta, Indonesia. Document study in qualitative research was employed as a research methodology in this study. The sources of data were obtained from the writings of intellectuals at FSH UIN Sunan Kalijaga. The analysis in this article was done by using Ṭāhā ‘Abdurraḥmān’s theory of integrative epistemology, through the integration between philosophical epistemology, i.e., subjective, objective, and intersubjective reasoning, and historical epistemology, i.e., early, middle, and late periods. The research found the integrative-intersubjective type of Islamic law studies as the scientific mentality of a Muslim jurist who is capable of creatively integrating subjective-objective-intersubjective reasonings and early-middle-late periods, to address issues of Islamic law in the contemporary era. This finding has implications in shaping a moderate reasoning of Islamic law studies, which is neither extremely subjective on the one hand nor extremely objective on the other. Epistemologi studi hukum Islam telah bergeser dari pola atomisasi ke arah integrasi. Integrasi epistemologi hukum Islam melingkupi tipe subjektif, objektif, dan intersubjektif. Model integrasi epistemologi di bidang ini telah menjadi diskursus penting di Universitas Islam Negeri (UIN) Sunan Kalijaga, Yogyakarta, Indonesia. Oleh karena itu, artikel ini mendiskusikan pergeseran paradigma pemikiran epistemologi studi hukum Islam di Fakultas Sharī’ah dan Hukum (FSH) Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, Indonesia. Metode penelitian menggunakan studi dokumen dalam penelitian kualitatif. Sumber data diambil dari tulisan-tulisan para pemikir di FSH UIN Sunan Kalijaga. Artikel ini dianalisis menggunakan teori epistemologi-integratif dari Ṭāhā ‘Abdurraḥmān, melalui integrasi antara epistemologi kefilsafatan (nalar subjektif, objektif, dan intersubjektif) dan epistemologi kesejarahan (nalar periode awal, pertengahan, dan akhir). Penelitian ini menemukan tipe studi hukum Islam integratif-intersubjektif sebagai mentalitas saintifik bagi seorang ahli hukum Muslim yang mampu mendialogkan secara kreatif antara nalar subjektif, objektif, intersubjektif dan nalar periode awal, pertenghan, dan akhir, untuk penyelesaian masalah hukum Islam di era kontemporer. Temuan ini berimplikasi pada pembentukan nalar studi hukum Islam moderat, yaitu tidak ekstrim subjektif di satu sisi dan ekstrim objektif di sisi yang lain.